Progress and Challenges for All‐Solid‐State Sodium Batteries - Hui-Ling Yang; Bin-Wei Zhang; Konstantin Konstantinov; Yun-Xiao Wang; Hua-Kun Liu; Shi-Xue Dou (Advanced Energy & Sustainability Research, 2021)
All‐solid‐state sodium batteries (ASSBs) are regarded as the next generation of sustainable energy storage systems due to the advantages of abundant sodium resources, and their exceptional and high energy density. Nevertheless, there are still grand challenges to realize their practical applications, such as the limited types of solid‐state electrolytes (SEs), low ionic conductivity of SEs, high charge‐transfer impedance, interfacial issues, and Na dendrite growth. Herein, the recent progress and challenges of various SEs for ASSBs are summarized, including solid polymer electrolytes, inorganic solid electrolytes (including oxides, sulfides, and boron hydrides), and their combinations. Furthermore, recent reports on various cathodes materials and corresponding cathode/SE interfacial issues are comprehensively reviewed. Current trends and future perspectives on sodium metal anodes are discussed in detail with an emphasis on the anode interface protection and innovative SEs with good Na compatibility. Finally, future opportunities for the development of ASSBs are outlined.